Moral reasoning among kindergarten students (Journal of the College of Basic Education, 2022)
The current research aims to identify: The current research aims to measure the level of moral defendment at the students of the Kindergarten section and identify differences in possessing moral debate according to the plane variable, for the first, second, third and fourth stages. The study sample consisted of a group of 400 students section (400) student distributors on (4) studies in the Mustansiriyah University Kindergarten section. Using appropriate statistical means The results have shown that the sample has a level of moral indication, and there is a statistical differences in possessing moral indication at least, in the light of the findings of the results The two researchers put a number of recommendations and proposals.